Antioxidant effect of alpha-lipoic acid against ethanol-induced gastric mucosal erosion in rats - YEGEN, BERRAK; ERZİK, CAN; ŞENER, GÖKSEL; YÜKSEL, MERAL; ÇETİNEL, ŞULE (KARGER, 2008)
Background/Aims: This investigation elucidates the role of free radicals in ethanol-induced gastric mucosal erosion and the protective effect of lipoic acid. Methods: After overnight fasting, Wistar albino rats were orally treated with 1 ml of absolute ethanol to induce gastric erosion. Lipoic acid (100 mg/kg) was given orally for 3 days before ethanol administration. Mucosal damage was evaluated 1 h after ethanol administration by macroscopic examination and histological analysis. Additional tissue samples were taken for measurement of malondialdehyde, glutathione (GSH), and myelo-per oxidase activity. Production of reactive oxidants and oxidant-induced DNA fragmentation and Na+,K+-ATPase activity were also assayed in the tissue samples. Results: Generation of reactive oxygen species and lipid peroxidation associated with neutrophil infiltration play an important role in the pathogenesis of gastric mucosal damage induced by ethanol. Furthermore, oxidants depleted tissue GSH stores and impaired membrane structure as Na+,K+-ATPase activity was inhibited. On the other hand, lipoic acid treatment reversed all these biochemical indices as well as the histopathological changes induced by ethanol. Conclusion: These data suggest that lipoic acid administration effectively counteracts the deleterious effect of ethanol-induced gastric mucosal injury and attenuates gastric damage through its antioxidant effects. Copyright (C) 2008 S. Karger AG, Basel.
Keywords: ethanol; gastric mucosal injury; lipoic acid; lipid peroxidation; SPINAL-CORD-INJURY; LIPID-PEROXIDATION; DIHYDROLIPOIC ACID; ISCHEMIA-REPERFUSION; FREE-RADICALS; CELL-DEATH; APOPTOSIS; DAMAGE; INFLAMMATION; SUPEROXIDE